Assesing Mobile Banking Application: The Extended Unified Theory of Acceptance and Use of Technology (UTAUT) - Arum Febriyanti Ciptaningtias; Prima Ayundyayasti (JURNAL ILMIAH EDUNOMIKA, 2026)
The advancement of technology enables mobile banking to become a possibility for the banking sectors, where adaptation of such information innovation can improve their service performance and customer satisfaction. This study aims to investigate and explore factors, which influence customers to use mobile banking in Semarang, Indonesia. The extending of a unified theory of acceptance and use of technology (UTAUT) is used as the primary model, where perceived risk and perceived access barriers are further appended into the model. After testing and validation, the questionnaire was distributed to university students (undergraduate and graduate students) and workers in Semarang, Indonesia. There are 300 questionnaires was usable for this research came from users and non-users of mobile banking services. The Goodness-of-fit (GOF) test was used to evaluate the model measurement. The outcomes of the survey are tested through structural equation modeling (SEM) to test the relationship between various factors involving in the adaptation of mobile banking in Semarang Indonesia. Findings certify that unified theory of acceptance and use of technology research model is appropriate to analyze mobile banking usage. It posits two significant determinants of intention to use mobile banking service, social influence (SI) and perceived access barriers (PAB) while facilitating condition (FC) as the powerful factor in use behavior (UB). Keywords- Mobile Banking, UTAUT, SEM